Intelligent Construction, Operation, and Maintenance of a Large Wastewater-Treatment Plant Based on BIM. (10th May 2021) - Li, Jiu-Lin; Chen, Li-Min; Xu, Hao
Abstract : Building information modeling (BIM) is a data-based tool for engineering, design, and building management, which is used to parameterize and model various types of information. This information may then be shared and introduced throughout the building life-cycle phases (planning, design, construction and operation, and maintenance (O&M)). Therefore, BIM allows engineers to correctly understand and efficiently respond to varying types of building information as well as serves as a foundation for cooperation between the design and construction teams. Hence, BIM plays an important role in increasing productivity, minimizing costs, and shortening construction times. In this article, we present a case example where BIM was used for intelligent construction of a large wastewater-treatment plant (WTP). The process involved intelligent design and simulation techniques, management and simulation of construction works, digital delivery solutions, BIM-based Internet of things O&M, and environmental monitoring. BIM was used to digitalize the construction, delivery, and O&M processes of the WTP. According to this case example, we also offer suggestions on how deep learning and intelligent control techniques can be used to enhance intelligent O&M in WTPs.